2016
DOI: 10.1007/s00221-016-4820-4
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and decay of visual capture and the ventriloquism aftereffect caused by brief audio-visual disparities

Abstract: Visual capture and the ventriloquism aftereffect resolve spatial disparities of incongruent auditory-visual (AV) objects by shifting auditory spatial perception to align with vision. Here, we demonstrated the distinct temporal characteristics of visual capture and the ventriloquism aftereffect in response to brief AV disparities. In a set of experiments, subjects localized either the auditory component of AV targets (A within AV) or a second sound presented at varying delays (1-20s) after AV exposure (A2 after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(89 citation statements)
references
References 43 publications
8
80
1
Order By: Relevance
“…In fact, most studies have relied on prolonged adaptation to multisensory discrepancies. Hence these studies investigated long-term recalibration, which seems to be mechanistically distinct from the trial-by-trial recalibration investigated here (7,18,19,27,28). The study most closely resembling the present one suggested that the ventriloquist after-effect is mediated by an interaction of auditory and parietal regions (18), a network centered view also supported by work on the McGurk after-effect (14,50).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In fact, most studies have relied on prolonged adaptation to multisensory discrepancies. Hence these studies investigated long-term recalibration, which seems to be mechanistically distinct from the trial-by-trial recalibration investigated here (7,18,19,27,28). The study most closely resembling the present one suggested that the ventriloquist after-effect is mediated by an interaction of auditory and parietal regions (18), a network centered view also supported by work on the McGurk after-effect (14,50).…”
Section: Discussionmentioning
confidence: 95%
“…Despite many behavioral studies demonstrating the robustness of multisensory trial-by-trial recalibration (6,7,9), little is known about the underlying neural substrate. Reasoning that recalibration relies on the persistence of information about previous stimuli, our study was guided by the quantification of where in the brain sensory information experienced during one trial can be recovered during the subsequent trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Bosen et al . ). The visual system is assumed to predominate within the process of spatial perception, with the auditory system being more influential in temporal perception (Morein‐Zamir et al .…”
Section: Discussionmentioning
confidence: 97%
“…Taken together, these results suggest how spatial calibration of the different senses occurs at the neuronal level. Vision is normally considered to be the most accurate and reliable amongst all the senses, and has been found capable of providing a reference for the calibration of auditory spatial perception (Zwiers et al 2003;Bosen et al 2017). The visual system is assumed to predominate within the process of spatial perception, with the auditory system being more influential in temporal perception (Morein-Zamir et al 2003;Recanzone, 2003;Spence & Squire, 2003;Eagleman, 2008).…”
Section: Discussionmentioning
confidence: 99%